Study of GaN nanorods converted from β-Ga2O3. (May 2018) - Li, Yuewen; Xiong, Zening; Zhang, Dongdong; Xiu, Xiangqian; Liu, Duo; Wang, Shuang; Hua, Xuemei; Xie, Zili; Tao, Tao; Liu, Bin; Chen, Peng; Zhang, Rong; et al.
Abstract: We report here high-quality β-Ga2 O3 nanorods (NRs) grown on sapphire substrates by hydrothermal method. Ammoniating the β-Ga2 O3 NRs results in strain-free wurtzite gallium nitride (GaN) NRs. It was shown by XRD and Raman spectroscopy that β-Ga2 O3 was partially converted to GaN/β-Ga2 O3 at 1000 °C and then completely converted to GaN NRs at 1050 °C, as confirmed by high-resolution transmission electron microscopy (HRTEM). There is no band-edge emission of β-Ga2 O3 in the cathodoluminescence spectrum, and only a deep-level broad emission observed at 3.68–3.73 eV. The band edge emission (3.39 eV) of GaN NRs converted from β-Ga2 O3 can also be observed. Graphical abstract: β-Ga2 O3 NRs synthesized by hydrothermal method are partially converted to GaN@β-Ga2 O3 at 1000 °C and then completely to GaN NRs at 1050 °C in NH3 atmosphere.Image 1 Highlights: High-quality gallium oxide NRs can be obtained by hydrothermal method. Ammoniating the β-Ga2 O3 NRs results in strain-free wurtzite gallium nitride NRs. Part or all of the gallium nitride phase can be formed by ammoniating gallium oxide at different temperatures.